2012
DOI: 10.1016/j.scr.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

DUXO, a novel double homeobox transcription factor, is a regulator of the gastrula organizer in human embryonic stem cells

Abstract: Human embryonic stem cells differentiate into gastrula organizer cells that express typical markers and induce secondary axes when injected into frog embryos. Here, we report that these human organizer cells express DUXO (DUX of the Organizer), a novel member of the double-homeobox (DUX) family of transcription factors, a group of genes unique to placental mammals. Both of DUXO's homeodomains share high similarity with those of Siamois and Twin, the initial inducers of the amphibian gastrula organizer. DUXO ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Nevertheless, D4Z4 homologs on chrs 3 and Y are divergent from each other and from 4q/10q D4Z4. Furthermore, sequence comparison of the recently discovered single‐copy DUXO gene on chr 3, which encodes DUX4c homolog [Sharon et al., ], revealed that the D4Z4 homolog on chr 3 amplified by our primer set is distinct from the DUXO gene (Supp. Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Nevertheless, D4Z4 homologs on chrs 3 and Y are divergent from each other and from 4q/10q D4Z4. Furthermore, sequence comparison of the recently discovered single‐copy DUXO gene on chr 3, which encodes DUX4c homolog [Sharon et al., ], revealed that the D4Z4 homolog on chr 3 amplified by our primer set is distinct from the DUXO gene (Supp. Fig.…”
Section: Resultsmentioning
confidence: 83%
“… 38 , 40 , 41 The DUXO gene may have a function in early development. 42 We therefore do not expect that reducing DUX4c and DUXO transcript levels in skeletal muscles will cause adverse effects; however, we could not assess this in the current study because DUX4c and DUXO are absent from the mouse genome.…”
Section: Discussionmentioning
confidence: 85%
“…Mouse Duxbl is critical for double negative thymocyte development and regulates myogenesis and reproductive development [ 20 22 ]. The human ortholog DUXO is a regulator of the gastrula organizer in human embryonic stem cells [ 23 ] and points to a role for DUX4 and repetitive elements in mammalian germline evolution [ 24 ]. The expression of DUX4 induces neurogenesis during differentiation of murine embryonic stem cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%